Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fnins.2020.00768
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional, Multisensory and Comprehensive Rehabilitation Intervention to Improve Spatial Functioning in the Visually Impaired Child: A Community Case Study

Abstract: Congenital visual impairment may have a negative impact on spatial abilities and result in severe delays in perceptual, social, motor, and cognitive skills across life span. Despite several evidences have highlighted the need for an early introduction of rehabilitation interventions, such interventions are rarely adapted to children's visual capabilities and very few studies have been conducted to assess their long-term efficacy. In this work, we present a case study of a visually impaired child enrolled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 94 publications
0
13
0
4
Order By: Relevance
“…A focus on such environmental adaptations would be recommended in home and school settings and, in general, in the child’s everyday environments. We believe such an approach, in line with current literature [ 43 ], would provide more insights on children’s functional vision, being worthy of consideration when planning tailored strategies in a multidimensional habilitation approach [ 70 , 72 ] for children with CVI.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A focus on such environmental adaptations would be recommended in home and school settings and, in general, in the child’s everyday environments. We believe such an approach, in line with current literature [ 43 ], would provide more insights on children’s functional vision, being worthy of consideration when planning tailored strategies in a multidimensional habilitation approach [ 70 , 72 ] for children with CVI.…”
Section: Discussionmentioning
confidence: 68%
“…No significant influence of oculomotor abilities on reading emerged from our analyses, probably due to the sample size and homogeneity. Nevertheless, reading abilities appear to be related to all the components of vision (perceptual, oculomotor, and cognitive) and may benefit from a comprehensive rehabilitation of these aspects from an early age [ 70 , 71 ]. We believe further studies on this topic are necessary, considering bigger samples of patients, attending different school grades and using homogeneous evaluation tools, to better define the learning profiles of children with CVI and reveal whether they could benefit from specific adaptations or training programs, also based on visual functioning.…”
Section: Discussionmentioning
confidence: 99%
“…for the early detection of signs of retinal degeneration or OMA) and for planning individualized rehabilitation tailored on the child's functional profile. 27,32 Studies are needed to unravel the role of visual function impairment in cognitive and adaptive development of children with Joubert syndrome. Romaniello et al previously reported challenges and barriers in daily life of adults with Joubert syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Other frequent neurological abnormalities were brisk deep tendon reflexes, electroencephalographic abnormalities, and altered respiratory patterns (short alternating episodes of apnoea and tachypnoea or episodic tachypnoea alone). Associated clinical features included ocular signs such as retinal dystrophy (defined according to current criteria 27,28 by poor vision, abnormal eye movements, poor pupil responses, fundus abnormalities involving macular, retinal vessels, and retinal pigmentation, abnormal ERG), renal involvement (congenital malformations, altered biochemical parameters, or overt nephronophthisis), liver abnormalities (elevated blood liver enzymes or liver fibrosis), endocrine signs (mainly short stature), cardiac malformations, altered brainstem auditory evoked potentials, and swallowing abnormalities. Facial dysmorphisms included prominent forehead, ptosis, prognathia, epicanthus, lower lip eversion with trapezoid-shaped mouth, tongue protrusion, and enophthalmos.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In this paper, we report on a critical single case characterized by a double risk condition for the parent-child interaction quality: the visual impairment of the child and the blindness of the father. We present this case as the dyad proceeds in its regulatory attunement as a system across a ten-session early intervention conducted at the IRCCS Mondino Foundation Developmental Neuro-ophthalmology Unit (Morelli et al, 2020 ). The micro-analytic coding of the dyadic exchange was carried on to highlight the progressive change in the relational functioning of a dyad who face a double-risk condition.…”
Section: Introductionmentioning
confidence: 99%